Politics of constituency development : challenges and perspectives - Theodore, Percita M. (Tamari Books OttawaCA, 1998)
Examines the correlation between the democratic political structure in the island state of St. Lucia and the non-implementation of development projects and plans at the regional level. Uses Vieux Fort the southern most town in St. Lucia, as a region and as an electoral constituency to measure the above correlation.